Colonial Echoes: The Politics and Paradoxes of English Medium Instruction in Sri Lankan Secondary Education - Wijesekera, H. (University of Jaffna, 2025)
The Sri Lankan educational landscape is shaped by historical, socio-political, linguistic, and economic factors. Typical in postcolonial countries, English enjoys a dominant place in society, particularly in education, where demand for English Medium Instruction (EMI) continues to rise. Reintroduced in 2003, six decades after independence from British rule, Sri Lankan Bilingual Education (BE) allows certain subjects in the national curriculum to be taught through EMI, while others are delivered in the mother tongue: Sinhala or Tamil. However, access to BE (and therefore EMI) remains highly restricted within the public school system, echoing colonial deliberations in the past, while fee-levying international schools offer full EMI instruction, exacerbating socio-economic inequalities through language: English. Within this complex educational landscape, BE reflects broader tensions between language, power, and equity in Sri Lanka. This paper examines the paradoxes in the implementation of EMI in Sri Lankan public schools, drawing on data from a broader qualitative study. The study employed multiple research tools, including surveys, focus group discussions, semi-structured interviews, and document analysis, to explore the perspectives of teachers, students, parents, and policymakers. Thematic content analysis was conducted using both inductive and deductive approaches to identify key patterns. Findings reveal significant disparities in the implementation of EMI (BE), primarily due to the absence of a coherent policy framework. Ministry of Education circulars often contain contradictory directives, reflecting a lack of informed decision- making and long-term strategic planning. Beyond systemic challenges such as a shortage of qualified EMI teachers and frequent, irrational teacher transfers, the study also uncovers active resistance within schools. Despite high demand, some school authorities obstruct EMI expansion due to ideological biases, bureaucratic inertia, or political motivations, further restricting access to English education for socio-economically disadvantaged students. These barriers raise serious concerns about equitable access to quality education and the continued role of English in perpetuating class- based privilege echoing the past ethos of the colonials. This study argues that EMI should be more widely accessible in public schools to address linguistic and socio-economic disparities. BE can also serve as a bridge for students from diverse ethnic backgrounds to learn together in a common language,helping to counteract the deep divisions created by a school system structured around mother tongue instruction. Yet, without well-structured policies and deliberate efforts to ensure equity, EMI risks reinforcing existing hierarchies threatening linguistic and education democracy rather than dismantling them. Expanding EMI access would contribute to the decolonization of English by transforming it from an elite-controlled linguistic commodity into a widely available educational resource. This shift is crucial to fostering a more inclusive and socially just education system. The paper concludes with policy recommendations focusing on teacher training, institutional support, and the need for a clearly defined, sustainable framework for EMI in Sri Lanka.
Keywords: English Medium Instruction; Bilingual Education; Language in education policies; Linguistic democracy; Sri Lanka